International directory of little magazines and small presses / . Directory of little magazines, small presses and underground newspapers (Dustbooks)
1-3rd ed. under the title: Directory of little magazines ; 4th ed. under the title: Directory of little magazines and small presses ; 6-8th ed. under the title: Directory of little magazines, small presses and underground newspapers. 5th ed. missing.